2004
DOI: 10.1039/b402977a
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsions with ionic liquid polar domains

Abstract: In this work 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF 4 ], an ionic liquid)/Triton X-100 (TX-100)/cyclohexane microemulsions have been prepared and characterized by phase behavior, conductivity measurement, dynamic light scattering, freeze-fracturing electron microscopy, and UV-vis techniques, and our attention is concentrated on the microemulsions with the ionic liquid as the nano-sized polar domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
305
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(331 citation statements)
references
References 29 publications
19
305
2
2
Order By: Relevance
“…[23][24][25][26] Gao et al were the first to discover that [bmim] [BF 4 ] assembles in polar nanosized droplets when dispersed in cyclohexane as solvent. 11 Recently, Han and his co-workers discovered that the 1,1,3,3-tetramethylguanidinium type of ILs can be dissolved in supercritical CO 2 reverse micelles. 27 They also reported that 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim] [PF 6 ]) can be dispersed in propylammonium formate (PAF), another type of IL.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Gao et al were the first to discover that [bmim] [BF 4 ] assembles in polar nanosized droplets when dispersed in cyclohexane as solvent. 11 Recently, Han and his co-workers discovered that the 1,1,3,3-tetramethylguanidinium type of ILs can be dissolved in supercritical CO 2 reverse micelles. 27 They also reported that 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim] [PF 6 ]) can be dispersed in propylammonium formate (PAF), another type of IL.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Usually, microemulsions are mixtures of non-polar solvents with polar liquids like water stabilized by a surfactant, 4,5 frequently in combination with a cosurfactant -often a short or medium chain alcohol 6 -forming an interfacial film that separates the two, in principle immiscible, solvents. 7 Though they are macroscopically homogeneous solutions, an ordered structure can be found on the nanoscopic scale such as oil-in-water (o/w) or water-in-oil (w/o) droplets, similar to the structures of micelles, [8][9][10] but with droplet sizes of 100 nm. 3 Besides droplets, lamellar, 11-13 random 14,15 or bicontinuous 3,16,17 microstructures, a network of water tubes in an oil matrix or a network of oil tubes in a water matrix have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Eastoe et al performed small angle neutron scattering (SANS) experiments on the same systems at 55°C, except that cyclohexane-d 12 was used to improve the scattering contrast (Eastoe et al, 2005). The scattering curves for different R values, comparable to the R values investigated by Gao et al (Gao et al, 2004) could well be described by a model of homogeneous diluted ellipsoidal particles, which was in agreement with IL/o structures. A swelling behavior of the IL nanodomains with increasing R value was observed consistent with the observations of Gao et al The SANS curves with the corresponding fits for ellipsoidal structures are illustrated in Figure 2.…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 53%
“…The first microemulsion, where water has been replaced by an RTIL has been reported by Gao et al (Gao et al, 2004). They replaced water by [bmim] [BF 4 ], while cylcohexane has been used as apolar phase and TX-100 as surfactant.…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation